Cinema between Latin America and Los Angeles : origins to 1960 - Gunckel, Colin, 1975-; Horak, Jan-Christopher; Jarvinen, Lisa, 1969- (Rutgers University Press, 2019)
Historically, Los Angeles and its exhibition market have been central to the international success of Latin American cinema. Not only was Los Angeles a site crucial for exhibition of these films, but it became the most important hub in the western hemisphere for the distribution of Spanish language films made for Latin American audiences. Cinema between Latin America and Los Angeles builds upon this foundational insight to both examine the considerable, ongoing role that Los Angeles played in the history of Spanish-language cinema and to explore the implications of this transnational dynamic for the study and analysis of Latin American cinema before 1960. The volume editors aim to flesh out the gaps between Hollywood and Latin America, American imperialism and Latin American nationalism in order to produce a more nuanced view of transnational cultural relations in the western hemisphere.